Ex-situ conservation of Cymbidium finlaysonianum by seed storage - DWI MURTI PUSPITANINGTYAS; ELIZABETH HANDINI (Society for Indonesian Biodiversity, 2020)
Abstract. Puspitaningtyas DM, Handini E. 2020. Ex-situ conservation of Cymbidium finlaysonianum by seed storage. Biodiversitas 21: 3519-3524. Cymbidium finlaysonianum Lindl. is an orchid that is native to Indonesia which has a pendulous flowers and relatively attractive colors. As a part of the Orchid Seed Storage for Sustainable Use (OSSSU) project, a preliminary study on seed of Cymbidium finlaysonianum Lindl. was conducted to test its viability at Bogor Botanic Gardens, Indonesian Institute of Sciences. The aim of this research was to evaluate the seed viability and to predict the seed longevity of C. finlaysonianum, after storage for different periods at freezing temperature-20°C. Storing of orchid seeds under cold conditions was the best conventional method in prolonging seed viability. Four different culture media were tested for asymbiotic germination. Seed viability was assessed after the seeds were stored for 0, 1, 2, 3, 6, 9, 12 months. Testing continued every year until there was no seed germination, and the viability was lost. The direct method of counting the number of germinating seeds was used to test seed viability. The result showed that seeds of C. finlaysonianum were able to germinate in 4 media i.e. Knudson C, modified Knudson C, modified Vacin & Went, and modified Hyponex fertilizer. The research showed that the viability seeds of C. finlaysonianum decreased after 2 years of storage, and the seeds were almost completely non-viable after six years of storage.